2015
DOI: 10.3174/ajnr.a4614
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Neovascularization after Indirect Bypass Surgery: Color-Coded Digital Subtraction Angiography in Pediatric Moyamoya Disease

Abstract: BACKGROUND AND PURPOSE:For the postoperative follow-up in pediatric patients with Moyamoya disease, it is essential to evaluate the degree of neovascularization status. Our aim was to quantitatively assess the neovascularization status after bypass surgery in pediatric Moyamoya disease by using color-coded digital subtraction angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Furthermore, the extent of neovascularization from the graft tissue was parallel to the changes in regional CBF [ 17 ]. Moreover, Cho et al [ 18 ] showed that the degree of neovascularization on cerebral angiographic images after indirect bypass surgeries correlated with clinical outcome. In cases of inadequate revascularization with symptoms of cerebral hypoperfusion, second salvage surgery should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the extent of neovascularization from the graft tissue was parallel to the changes in regional CBF [ 17 ]. Moreover, Cho et al [ 18 ] showed that the degree of neovascularization on cerebral angiographic images after indirect bypass surgeries correlated with clinical outcome. In cases of inadequate revascularization with symptoms of cerebral hypoperfusion, second salvage surgery should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The most effective treatment for MMD is extracranial-intracranial (EC-IC) revascularization surgery including direct bypass, indirect bypass, or combined bypass techniques [ 2 , 3 ]. The direct bypass or the combined bypass can improve intracranial perfusion by instantly increasing cerebral blood flow while later de novo collateral vessels will form from the indirect/extracranial graft, and it is increasingly considered more effective than only indirect treatment strategies for MMD patients [ 4 6 ]. Previous studies have reported that neoangiogenesis in the surgical area, reduced moyamoya vessels and improved intracranial perfusion (examined by postoperative computed tomography perfusion [CTP]), could be found during follow-up [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative color-coded parametric DSA (QDSA, Syngo iFlow) is an emerging DSA technique which provides objective perfusion parameters like time-to-peak (TTP), mean transit time (MTT), and ratios of area under the curve (AUC ratio) to assess hemodynamic changes of a certain artery after bypass surgery. Although it does not provide information on cerebral parenchyma perfusion, it is useful for measuring blood supply from the internal and external carotid artery systems [8,9]. However, DSA is not recommended for pediatric patients or patients in poor conditions, due to its invasiveness, time consumption, and need for anesthesia.…”
Section: Digital Subtraction Angiography (Dsa)mentioning
confidence: 99%